Pengaruh Penggunaan Internet Banking Dan Perlindungan Data Nasabah Terhadap Cybercrime Di Kota Denpasar - Dewa Ayu Pargita Apsari; Ni Putu Suci Meinarni; Wayan Gede Suka Parwita (Jayapangus Press, 2021)
This study aims to determine the effect of Internet Banking Usage and Data Protection of Internet Banking Users on Cybercrime in Denpasar. This study uses data collection techniques by distributing questionnaires online. The population in this study were users of internet banking facilities in the Denpasar area with a sample of 72 respondents. To obtain correct data for conclusions that are in accordance with the actual situation, it is necessary to have an instrument that is valid and consistent and appropriate in providing research data. Where the instrument validity test in this study uses Product Moment Correlation, while the reliability test uses Cronbach Alpha. The analysis technique used is the multiple Linear Regression Analysis technique, namely with 5 variables X and 1 variable Y. The results show that there is no significant effect of Internet Banking Usage and Customer Protection of Internet Banking Facility Users (Client Charter, Confidentiality of Customer Data, Test and Trial Drive, and Customer Support Service) together on the occurrence of Cybercrime in the Denpasar area with an Fcount value of 1.173 with a significance value of F of 0.332